Assessment of multivariate associations and spatial variability of forest soil properties and their stand factors in the Czech Republic - Vincent Oppong Sarkodie; Radim Vašát; Karel Němeček; Vít Šrámek; Věra Fadrhonsová; Kateřina Neudertová Hellebrandová; Luboš Borůvka (Soil and Water Research)
Knowing the relationship between forest soil properties and their stand conditions is relevant for the sustainable exploitation and management of forest soils. This study examines the influence of stand environmental factors on soil properties within forest environments. We further assessed the spatial variability of these soil properties and their controlling factors. A harmonised soil database on the entire forest areas of the Czech Republic was considered; however, only 851 sampling points with complete data on soil properties was used out of the more than 8 thousand sampling points in the database. The topsoil mineral layer of 0-30 cm was analysed. Principal component analysis was used to determine the relationships between the forest soil properties and their stand controlling factors. The nugget ratios for the semivariograms and cross-variograms were used to evaluate the spatial dependence of soil properties, and their relevant controlling factors. Forest types influence soil reaction and the availability of cations within the topsoils. Phosphorus is influenced by aluminium and cation exchange capacity. There are higher concentrations of total phosphorus and aluminium under broadleaved forest.